Coping Trajectories and the Health-Related Quality of Life of Childhood Cancer Survivors. (19th March 2021) - Fisher, Rachel S; Sharp, Katianne M Howard; Prussien, Kemar V; Himelhoch, Alexandra C; Murphy, Lexa K; Rodriguez, Erin M; Young-Saleme, Tammi K; Vannatta, Kathryn; Compas, Bruce E; Gerhardt, Cynthia A
Abstract: Objective : To identify coping trajectories from diagnosis through survivorship and test whether particular trajectories exhibit better health-related quality of life (HRQOL) at 5 years post-diagnosis. Methods : Families of children with cancer (ages 5-17; M = 10.48, SD = 4.03) were recruited following a new diagnosis of cancer ( N  =   248). Three follow-up assessments occurred at 1-year ( N  =   185), 3-years ( N  =   101), and 5-years ( N  =   110). Mothers reported on children's coping using the Responses to Stress Questionnaire for Pediatric Cancer. Survivor HRQOL was measured at 5-year follow-up using self-report on the PedsQL 4.0. Longitudinal patterns of coping were derived using Latent Class Growth Analysis and mean-levels of survivor-report HRQOL were compared across classes. Results : Two primary control coping trajectories emerged, "Moderate and Stable" (50%) and "Low-moderate and Decreasing" (50%), with no significant differences in HRQOL across trajectories. Three secondary control coping trajectories emerged, "Moderate-high and Increasing" (54%), "Moderate and Stable" (40%), and "High and Increasing" (6%), with survivors in the last trajectory showing better HRQOL. Two disengagement coping trajectories emerged, "Low and Stable" (85%) and "Low and Variable" (15%), with no significant differences in HRQOL across trajectories. Conclusions : Coping trajectories were relatively stable from diagnosis to 5 years. A small group of survivors with high and increasing secondary control coping over time, per mother-report, reported better HRQOL. Future research should consider tailoring coping interventions to children with cancer to improve survivors' HRQOL.